(untitled) (Revista científica Olimpia, 2020)
The Sports Artistic Gymnastics is a part of the development that has had an operation in the area of physical culture and the sport, at the present time this mode pertaining to sports has kept on evolving attaining a lofty progress, bringing like consequences a tall level of requirements, a high mastery as of execution and an increase in the degree of difficulty of all the technical elements, this is a sport of appreciation and demands the correct technique of the exercises and its corresponding assessment. Exercises combined of great complexity and range of motion in order to offer to the spectator come true and to the umpires a selection with deftness, dynamism and expressiveness, in addition to the utilization of the music in the case of the exercises to hands off, it is for this motive than in this article shows up a set of developmental exercises of flexibility, in the athletes of sports artistic gymnastics in the gymnastics school of the Bayamo Municipality, Granma Province. For the design of said exercising set the following scientific methods were used: Of the theoretic level the historic logician, analysis synthesis, inductive deductive, also employed themselves as the ones of the empiric level the observation (non-structured), pre experiment, measurement and in the statistician was used the statistical package SPSS version 11,5 and the test not parametric of Wilcoxon.